Determination of compounding formulation of cured rubber by reverse engineering. Issue 6 (15th April 2015) - Datta, Sanjoy; Stoček, Radek; Kuřitka, Ivo; Sáha, Petr
<x xml:space="preserve">Abstract</x> The present work deals with reverse engineering on four rubber formulations. Information about the material composition of the compounding formulations was obtained by using techniques such as acetone extract, thermogravimetric analysis, energy dispersive X‐ray fluorescence studies, and Fourier transform infrared (FTIR) spectroscopy in attenuated total reflection mode. The reverse engineered formulations were compared on a qualitative and quantitative basis with the initial formulations. The aim was to ascertain the validity of the methodology, which may be used as reverse engineering of rubber compounds to quantitatively analyze unknown ground tire rubber in future. The state of the art was based on a fractional mass transfer from acetone extract to the rubbers detected in TGA. Through this new approach, the formulations calculated were very consistent with the formulations employed, thus establishing the validity of the methodology used. POLYM. ENG. SCI., 55:1450–1458, 2015. © 2015 Society of Plastics Engineers